Compensation Management in An Effort to Improve Education Performance in Cikarang Technical Vocational School, Bekasi District - Nasuha, Ahmad; Hermanto; Vomit (Proceeding International Conference on Education, 2023)
This study aims to analyze compensation management in an effort to improve the performance of education personnel at SMK Teknikom Cikarang. This research uses a qualitative method. Data collection methods were conducted through observation, interviews and documentation. Data analysis techniques include data collection, data reduction, data presentation, and verification. This research resulted in conclusions: 1) The form of compensation for educators at SMK Teknikom Cikarang is given in four forms of compensation, namely wages, salaries, allowances, and incentives; 2) Stages in the implementation of the compensation system at SMK Teknikom Cikarang start from analyzing positions, how to determine compensation and how to provide compensation; 3) The performance of education personnel can increase after the implementation of the compensation system at SMK Teknikom Cikarang. From the results of the study it can be concluded that the implementation of good compensation management, namely in a planned and objective manner, can improve the performance of educational personnel. Therefore, educational institutions need to pay attention to compensation management as an effort to improve the performance of education personnel which can have an impact on improving educational services for students.